The Representation of Liberal Feminism through the Main Character in “The Post” Movie - Nur Azizah; Nurul Fitri (JELT: Journal of English Language Teaching, 2019)
This research is aimed to find out representation of liberal feminism through the main character. This research used qualitative descriptive method and focused Marilley theory. The researcher used feminism concept to identify how the liberal feminism is presented in the movie. The supporting data were obtained from some sources, such as books, articles, and journals, related to gender discrimination, women‘s stereotypes, and feminism. In collecting the data, read-write technique was used. The data analysis was conducted using feminism approach. The researcher found that there are three types of liberal feminism. First the feminism of equal rights, second the feminism of fear, and last the feminism of personal development, in this research is dominant with feminism of personal development and liberal feminism representation in the movie.Keywords: Liberal Feminism, Main Character.